1991
DOI: 10.1093/brain/114.5.2037
|View full text |Cite
|
Sign up to set email alerts
|

MATURATION OF HUMAN CEREBRUM OBSERVED IN VIVO DURING ADOLESCENCE

Abstract: SUMMARYIn the present study using magnetic resonance imaging (MRI), age changes in the morphology of the cerebral cortex, greatest in the frontal and parietal convexities, were observed during adolescence. Results suggest that increases in cerebrospinal fluid (CSF) within the sulci of these cortical regions accompany grey matter decreases. Smaller reductions in volume are also observed in subcortical grey matter nuclei. These apparent grey matter volume reductions presumably reflect processes of late brain mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
227
2
5

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(255 citation statements)
references
References 26 publications
21
227
2
5
Order By: Relevance
“…Our results indicate that children who already showed secondary characteristics of puberty as compared with those who did not have decreased gray matter density mainly in (pre-) frontal and parietal areas. Indeed, in earlier studies, frontal and parietal gray matter decreases have been shown around the onset of puberty (although direct measures of puberty were not reported) Jernigan et al, 1991]. It has been suggested that the decrease of gray matter represents the process of synaptic pruning, i.e., elimination of neuronal connections which are infrequently used [Paus, 2005].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results indicate that children who already showed secondary characteristics of puberty as compared with those who did not have decreased gray matter density mainly in (pre-) frontal and parietal areas. Indeed, in earlier studies, frontal and parietal gray matter decreases have been shown around the onset of puberty (although direct measures of puberty were not reported) Jernigan et al, 1991]. It has been suggested that the decrease of gray matter represents the process of synaptic pruning, i.e., elimination of neuronal connections which are infrequently used [Paus, 2005].…”
Section: Discussionmentioning
confidence: 97%
“…The pubertal period partly overlaps with adolescence, but is usually referred to as the period during which behavioral, cognitive, and emotional changes arise as well [Sisk and Zehr, 2005]. During the course of childhood and adolescence, prominent brain changes take place in the proportion of gray and white matter within the cerebrum: region-specific gray matter decreases have been reported Gogtay et al, 2004;Jernigan et al, 1991;O'Donnell et al, 2005;Sowell et al, 2002Sowell et al, , 2004Thompson et al, 2000;Wilke et al, 2007], as well as white matter increases [Barnea-Goraly et al, 2005;Giedd et al, 1999;Paus et al, 1999;Thompson et al, 2000]. Especially, around the onset of puberty, global gray matter as well as frontal and parietal gray matter Jernigan et al, 1991] start to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has revealed that frontal regions including medial prefrontal cortex, orbitofrontal cortex, amygdala, and ventral hippocampus, as well as dopamine input to these regions [6,9,11,19,24,26], play an important role in peer-directed social interactions. These brain regions are among those that undergo considerable remodeling during adolescence [1,15,16,18,35,37,48,49] and, hence are likely targets for contributing to the disruption in social preference following chronic adolescent exposure to ethanol. Indeed, there are a number of reports that ethanol-induced damage in these and other brain regions may be more pronounced during adolescence than in adulthood [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…Brain regions undergoing particularly marked changes in human adolescents and their counterparts in other species include the prefrontal cortex [16,37,49] and limbic and mesolimbic brain systems [15,18], regions that form important substrates for modulating responsiveness to alcohol and other drugs of abuse. The risk of extensive alcohol use is increased during adolescence, with 12% of 8 th graders, 22% of 10 th graders, and one fourth of 12 th graders (25%) reporting binge drinking (i.e., five or more drinks per occasion) during the past 2 weeks [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are further volume increases through puberty (Caviness, Kennedy, Richelme, Rademacher, & Filipek, 1996). Beyond puberty, there is actually a reduction in gray matter volume, likely associated with synaptic pruning and other regressive processes (Gogtay et al, 2004;Huttenlocher, 1990;Jernigan, Trauner, Hesselink, & Tallal, 1991). In contrast, white matter volume increases linearly with age (Giedd et al, 1999).…”
mentioning
confidence: 99%